(untitled) (Nigerian Journal of Technology, 2025)
Estimating the margin for voltage collapse is a critical concern for power system utility companies and stakeholders in developing power systems. A common approach uses Euclidean distance in continuation power flow to address singularity-induced network constraints. However, this method fails to capture exact topological properties, leading to overly conservative stability margin predictions. To overcome these limitations, this study introduces the arc-length path to the existing model, leveraging numerical simulations with varying step sizes. The optimal step size value was determined through various simulations, including 19 incremental step size adjustments and 8-step size reductions. The results of these simulations validated the findings. Notably, combining arc length and Euclidean distance for margin estimation reveals that the latus rectum, corresponding to local parameterization, and the margin to voltage collapse are equidistant from the saddle-node bifurcation point.